The Role of Entrepreneurship Education, Community-Based Mentorship, and Social Capital on the Independence of Social Creative Businesses in Jakarta - Masri, Marius; Apriyanto, Apriyanto; Lesmana, Tera (Westscience Press, 2025)
This study examines the impact of entrepreneurship education, community-based guidance, and social capital on the independence of social creative businesses in Jakarta. Using a quantitative approach, data were collected from 150 respondents and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results demonstrate that all three factors significantly contribute to the independence of social creative businesses. Entrepreneurship education equips entrepreneurs with essential skills and knowledge, while community-based guidance fosters collective problem-solving and resource sharing. Social capital emerges as the strongest predictor, emphasizing the importance of trust and networks in achieving entrepreneurial autonomy. These findings underscore the need for targeted policies and programs to support the growth and sustainability of social creative businesses in Jakarta.